Use of rice husk for the adsorption of congo red from aqueous solution in column mode - Han, Runping; Ding, Dandan; Xu, Yanfang; Zou, Weihua; Wang, Yuanfeng; Li, Yufei; Zou, Lina (Bioresource technology, 2008)
A continuous fixed bed study was carried out by using rice husk as a biosorbent for the removal of congo red (CR) from aqueous solution. The effects of important factors, such as the value of initial pH, existing salt, the flow rate, the influent concentration of CR and bed depth, were studied. Data confirmed that the breakthrough curves were dependent on flow rate, initial dye concentration and bed depth. Thomas, Adams–Bohart, and Yoon–Nelson models were applied to experimental data to predict the breakthrough curves using non-linear regression and to determine the characteristic parameters of the column useful for process design, while bed depth/service time analysis (BDST) model was used to express the effect of bed depth on breakthrough curves. The results showed that Thomas model was found suitable for the normal description of breakthrough curve at the experimental condition, while Adams–Bohart model was only for a initial part of dynamic behavior of the rice husk column. The data were in good agreement with BDST model. It was concluded that the rice husk column can remove CR from solution.